Effect of Al-doped ZnO or Sn-doped In2O3 electrode on ferroelectric properties of (Pb, La)(Zr, Ti)O3 capacitors. (8th April 2015) - Takada, Yoko; Tsuji, Toru; Okamoto, Naoki; Saito, Takeyasu; Kondo, Kazuo; Yoshimura, Takeshi; Fujimura, Norifumi; Higuchi, Koji; Kitajima, Akira; Iwai, Hideo
Abstract: Using chemical solution deposition, we fabricated ferroelectric (Pb, La)(Zr, Ti)O3 (PLZT) capacitors with either Al-doped ZnO (AZO) or Sn-doped In2 O3 (ITO) top electrodes. Then, the effects of a thin conductive AZO or ITO buffer layer between the Pt bottom electrode and PLZT thin film were investigated in combination with an AZO or ITO top electrode (AZO/PLZT/AZO/Pt and ITO/PLZT/ITO/Pt). The H2 degradation resistance of the AZO/PLZT/AZO/Pt and ITO/PLZT/ITO/Pt capacitors was improved. For AZO/PLZT/AZO/Pt capacitors with 10- and 20-nm-thick buffer layers, the H2 degradation resistance was 91 and 81%, respectively, compared with 42–70% without a buffer layer. The H2 degradation resistance of ITO/PLZT/ITO/Pt capacitors with a 28-nm-thick buffer layer was improved to 85% from 60–76% without a buffer layer. The time-of-flight secondary ion mass spectrometry depth profile indicated that AZO is the better H2 barrier after forming gas (3% H2 /balance N2 ) annealing.